Procalcitonin levels in patients with positive blood culture, positive body fluid culture, sepsis, and severe sepsis: a cross-sectional study. Issue 1 (2nd January 2016) - Yu, Ying; Li, Xia-Xi; Jiang, Ling-Xiao; Du, Meng; Liu, Zhan-Guo; Cen, Zhong-Ran; Wang, Hua; Guo, Zhen-Hui; Chang, Ping
Abstract : Background: Numerous investigations on procalcitonin (PCT) have been carried out, although few with large sample size. To deal with the complexity of sepsis, an understanding of PCT in heterogeneous clinical conditions is required. Methods: Hospitalized patients aged 10–79 years were included in this retrospective and cross-sectional study. PCT tests were assayed within 2 days of blood culture. Results: A total of 2952 cases (from 2538 patients) were enrolled in this study, including 440 cases in the 'positive BC' group, 123 cases in the 'positive body fluid culture' group, and 2389 cases in the 'negative all culture' group. Median PCT values were 4.53 ng/ml, 2.95 ng/ml, and 0.49 ng/ml, respectively. Median PCT values in the gram-negative BC group and gram-positive BC group, respectively, were 6.99 ng/ml and 2.96 ng/ml. Median PCT values in the 'positive hydrothorax culture' group, 'positive ascites culture' group, 'positive bile culture' group, and 'positive cerebrospinal fluid culture' group, respectively, were 1.39 ng/ml, 8.32 ng/ml, 5.98 ng/ml, and 0.46 ng/ml. In all, 357 cases were classified into the 'sepsis' group, 150 of them were classified into the 'severe sepsis' group. Median PCT values were 5.63 ng/ml and 11.06 ng/ml, respectively. Conclusions: PCT could be used in clinical algorithms to diagnose positive infections and sepsis. Different PCT levels could be related to different kinds of microbemia, different infection sites, and differing severity of sepsis.